Figure 1 from: Elias RB, Brito MR, Pimentel CM.M, Nogueira EC, Borges PA (2019) Biota from the coastal wetlands of Praia da Vitória (Terceira, Azores, Portugal): Part 4 – Vascular plants. Biodiversity Data Journal 7: e38687. https://doi.org/10.3897/BDJ.7.e38687 - Elias, Rui; Brito, Mariana; Pimentel, César; Nogueira, Elisabete; Borges, Paulo (Zenodo, 2019)
Figure 1 Location of the study areas in Terceira island: ■ Paul da Praia da Vitória (PPV); ○ Paul do Belo Jardim (PBJ); ● Paul da Pedreira do Cabo da Praia (PPCP). The geographical setting of the Azores islands and the location of the archipelago in the North Atlantic Ocean are also shown.